1971
DOI: 10.1021/jm00284a005
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin derivatives. 1. Preparation of mitosane and mitosene compounds and their biological activities

Abstract: Several derivatives of mitomycin were prepared from natural mitomycins and subjected to antibacterial tests. The structure-activity relationship was investigated for enzymatic activation, inhibition of DNA synthesis, and prophage induction. Substituents X, Y, and Z in mitomycins (1) are closely related to the rate of activation, which has a great effect on the biological activity. The aziridine group is responsible for inhibition of DNA synthesis and also for alkylating actions of mitomycins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…Other work related its activity to suppression of B-lymphocyte activation which suggested Imexon to be useful in the treatment of B-cell or plasma cell lymphomas or neoplasias, certain autoimmune disorders and infection with Rauscher leukemia virus [ 18 , 19 ]. Natural aziridine alkaloids, as well as their lipophilic semi-synthetic, and synthetic analogs, in addition to antitumor activity, have also a strong antibacterial activity [ 20 ]. Well known mitomycin A, C and mitosane compounds show antimicrobial activity primarily against Gram-positive bacteria and Klebsiella pneumoniae [ 10 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other work related its activity to suppression of B-lymphocyte activation which suggested Imexon to be useful in the treatment of B-cell or plasma cell lymphomas or neoplasias, certain autoimmune disorders and infection with Rauscher leukemia virus [ 18 , 19 ]. Natural aziridine alkaloids, as well as their lipophilic semi-synthetic, and synthetic analogs, in addition to antitumor activity, have also a strong antibacterial activity [ 20 ]. Well known mitomycin A, C and mitosane compounds show antimicrobial activity primarily against Gram-positive bacteria and Klebsiella pneumoniae [ 10 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although MTC forms cross-links between complementary strands of DNA, the majority of mitomycin residues attach to DNA by a monofunctional alkylation in which one antibiotic molecule is attached to a single base (27), and nothing is known about the action of mitomycin residues attached monofunctionally to one strand of DNA. For the purpose of understanding the repair mechanism of crosslinked DNA on the one hand, and of understanding the action of mitomycin residues attached to DNA by a monofunctional alkylation on the other, 7-methoxymitosene 1,2,11) and decarbamoyl mitomycin C (DCMTC; 12), which have been assumed to act as a monofunctional alkylating agent (24), were used in this study. We present evidence that they produce DNA damage which results in the production of DNA strand breaks.…”
mentioning
confidence: 99%
“…Although this scheme was suitable for the synthesis of aziridinomitosanes, a venture to introduce the C9a heteroatom functionality (essential for activity [85]) was attempted unsuccessfully in this study. The same authors observed that any attempts to oxidize a leucoaziridinomitosane of type 86 via a Polonovski reaction inevitably gave either the corresponding leucoaziridinomitosene 88 or the oxidation product at C3, 89 (Scheme 24) [86].…”
Section: Discussionmentioning
confidence: 99%
“…This compound has shown anti-tumour and anti-bacterial activities and thus is a valid target for a synthesis [85]. Being completed just after the period culminating in the synthesis of Vitamin B12 by the groups of Woodward and Eschenmoser [130], this synthesis utilized a powerful methodology developed during this period to make vinylogous amides [131132].…”
Section: Discussionmentioning
confidence: 99%